(untitled) (World Economics and Finance Bulletin, 2023)
The study aims to analyze and measure the impact of some monetary policy variables (wide money supply (M2), foreign currency window sales and foreign reserves) on the Iraqi dinar exchange rate, and to know the impact of these monetary variables on the Iraqi dinar exchange rate, during the period (2004-2021) and based on standard analysis methodology .